1993
DOI: 10.1139/b93-183
|View full text |Cite
|
Sign up to set email alerts
|

Redifferentiation of moss protonemata: an experimental and immunofluorescence study of brood cell formation

Abstract: The formation of ovoid or spherical brood cells from chloronemal filaments by swelling and symmetrical subapical divisions preceded by phragmosomes, but not preprophase bands, is described in the mosses Physcomitrella patens, Dicranoweisia cirrata, Bryum tenuisetum, Bryum bicolor, and Rhytidiadelphus loreus. This is a widespread phenomenon that occurs in protonemal colonies cultured for long periods of time or allowed to dry out. It involves the redifferentiation of highly polarized chloronemal cells with a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 33 publications
3
38
1
Order By: Relevance
“…Indirect immunofluorescence studies with a-tubulin antibody confirm the presence of net axial arrays of MTs in control cells, as described previously (Doonan, 1991;Goode et al, 1993) (Fig. 7a-c).…”
Section: Fluorescence Microscopysupporting
confidence: 81%
See 1 more Smart Citation
“…Indirect immunofluorescence studies with a-tubulin antibody confirm the presence of net axial arrays of MTs in control cells, as described previously (Doonan, 1991;Goode et al, 1993) (Fig. 7a-c).…”
Section: Fluorescence Microscopysupporting
confidence: 81%
“…The cytological responses of brood cells, desiccation-tolerant propagules (Goode et al, 1993), to drying and rewetting have been reported and discussed elsewhere (Rowntree et al, 2007).…”
Section: New Phytologistmentioning
confidence: 99%
“…ABA treatment of protonema cells of various moss species for several days has been shown to induce structural changes leading to the formation of spherical, thick-walled brood cells (Goode et al, 1992). Thus, we observed ABA-induced changes of protonema cells in transgenic P. patens expressing MpABI1 and MpABI1-d2.…”
Section: Aba-induced Morphological Changes In Transgenic Plantsmentioning
confidence: 56%
“…It has been shown that new proteins accumulate in F: hygrometrica following ABA treatments (Bopp and Werner, 1993;Werner and Bopp, 1993). Goode et al (1992) reported the acquisition of similar desiccation tolerance in a number of mosses, including P patens, following ABA application.…”
Section: Discussionmentioning
confidence: 99%